Ruling on imamating a prostitute in prayer Comparative Juristic Study - امير محمد حسن (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
This research came to clarify and explain the concept of imamah in prayer and its place in the Islamic law, citing the Quranic verses, the prophetic Hadiths, and the scholars’ sayings. It is well known that in recent times after the infighting of doctrinal and doctrinal ideas as well as radical nationalism in Iraq, which led to the corruption of society and the destruction of its people and destruction of destruction and looting and displacement, all because of the word fired by its detractors to others ignorant or falsified, Fermi people infidelity and blood and money , So we feel the danger of this slippery, which is still presented by many Muslims, standing or sitting, newly and old, the release of infidelity and innovation to the imams and preachers without the controls of legitimacy set by the scientists of the conditions and prohibitions, , And then atone for them And their coordination, has occurred in many mosques today ?! From here I saw the duty to invite me to write this research to clarify the words of the scholars of the Salaf and Khalaf in prayer behind the imam of the abomination, and to present their evidence and the most correct view of it. May God help us and protect us from bad deeds and deeds.